Investing in dynamic markets : venture capital in the digital age - Kressel, Henry; Lento, Thomas V. (Cambridge : Cambridge University Press, 2010)
'Without venture capital, many of the companies whose technical innovations sparked the digital revolution would not exist. Venture investments funded these firms to develop their bright ideas into commercial products that created new business models and established whole new markets. In Profiting from Innovation, Henry Kressel, a partner at multi-billion-dollar global investing company Warburg Pincus, takes you behind the scenes of the private equity process. He draws on his extensive experience to show how venture capital works, why venture capitalists fund certain companies and not others, and what factors influence the success or failure of their high-risk, high-reward investments. He also discusses venture capital's future, now that the commercialization of technology requires larger investments and global market access. Written in clear, non-technical language, the book features informative case studies of venture capital funding in a wide range of industries, including telecommunications, software and services, semiconductors, and the internet'--
Includes bibliographical references and index.
Keywords: Venture capital; High technology industries; Investments -- Computer network resources